Engaging with the clinical data transparency initiative: a view from the National Institute for Cardiovascular Outcomes Research (NICOR) - Clive Weston (Heart, 2012)
In this editorial we address the Coalition Government's 'transparency initiative' and point to the issues raised in presenting and interpreting raw data on hospital and practitioner performance to the public and to commercial organisations.